PERTANGGUNGJAWABAN PIDANA KORPORASI DALAM PERKARA NOMOR: 1066 K/PID.SUS/2017 ATAS TINDAKAN MENAMBANG DI LUAR WILAYAH IZIN USAHA PERTAMBANGAN - Duo Putra Njoto, Enricho; Suhartono, Slamet; Herlyn Setyorini, Erny (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
The topic of discussion of mining crimes outside the permitted area is discussed to address issues related to corporate criminal liability in case Number: 1066 K / PID.SUS / 2017 for mining actions outside the mining business permit area. Research with issues of corporate criminal liability in case Number: 1066 K / PID.SUS / 2017 for mining activities outside the mining business permit area, the following conclusions are obtained:Whereas although a person (the company management) does not commit a criminal act himself and does not have an error in the ordinary sense, it can be accountable. Managers do, managers and corporations are criminally responsible for the actions that occur, namely the felling of trees in production forests for mining even though they are outside the permitted location.Mining outside the permitted area, which means the destruction of the forest and the environment has been damaged, therefore the perpetrators should be charged simultaneously so that criminal sanctions will be more severe and deterrent. In connection with the perpetrators of the crime as the main director, the sanctions imposed not only on the management but also on the corporation as additional crimes other than the main crime.